المنهاج الصوفي ودوره في إصلاح آليات التعامل مع كتاب الله تعالى: Sufis Methodology and Its Role in Reforming the Mechanisms of Dealing with al-Quran - Sayyed Ali al-Mahdaly, Sayyed Abdul Hamid; Syed Abdul Rahman, Syed Mohammad Hilmi (Afkar: Jurnal Akidah dan Pemikiran Islam, 2015)
The article tries to highlight the nature of al-Islah based on Islamic point of view to the assertion that it must be the starting point of the Qur’an, realized by the Prophet Muhammad p.b.u.h. in the reality of life through his great character. Then it was followed by his companions by utilizing it as the methodology of science in determining fiqh al-Kitab and Sunnah. It is also used as a basis to guide the people to obey the truth. Thus they struggled to raise this noble religion and they are confident that the glory belongs only to Allah and the believers who keep their promise to God that they successfully lead the worldly affairs as well as the hereafter. All of it was the results of the divinity tutelage prominently in the reform of society to transform human beings that follow-up would result in changes to the entire human life. Any damage occurring in the Muslim community throughout the ages until today is due to heart damage that prevents them to understand the divine secrets as a bridge for all human growth in this world and hereafter. Hence the Muslims scholars who give efforts to enhance community have taken the right step to take advantage of athar al-Salaf al-Salih in establishing a comprehensive methodology of knowledge in purify and boost the heart. Sufi scholar methodology inferred from the texts of legislation contained in it all the methods and principles of divinity is the only methodology that is able to respond to the demands of the human soul. Neglect of this methodology can bring the whole future of mankind toward destruction.